Active screening of gastrointestinal helminth infection in migrant workers in Thailand. Issue 11 (November 2018) - Kaewpitoon, Soraya J; Sangwalee, Wararat; Kujapun, Jirawoot; Norkaew, Jun; Chuatanam, Jirayut; Ponphimai, Sukanya; Chavengkun, Wasugree; Padchasuwan, Natnapa; Meererksom, Thirayu; Tongtawee, Taweesak; Matrakool, Likit; Panpimanmas, Sukij; et al.
Objective: This study aimed to detect gastrointestinal helminth infection in migrant workers in Thailand. Methods: A cross-sectional survey study was conducted in 403 migrant workers in the factories of Nakhon Ratchasima Province, northeastern Thailand during October 2016 to June 2017. Gastrointestinal helminth infections were detected by the formalin ether acetate concentration technique and microscopy. The data were analyzed using the χ 2 -test and logistic regression. Results: The rate of gastrointestinal helminth infection was 24.07%. The most common species involved in infection was O pisthorchis viverrini (11.91%), followed by hookworm (5.46%), Trichuris trichiura (5.21%), Strongyloides stercoralis (0.5%), Ascaris lumbricoides (0.5%), and Taenia spp. (0.5%). The majority of infections were found in men aged ≥40 years, married participants, uneducated participants, laborers, those who worked for 1 year, and those who had an income of 9000 to 12, 000 THB. Conclusions: Gastrointestinal helminth infection is still found in migrant workers. Therefore, active surveillance is required in this large group for investigating and eradicating this type of infection.